Neoconstitutionalism or contemporary constitutionalism as a legal theory and the new role of judges - Cotrina Maccha, Manuel Jesús (2018)
Neoconstitutionalism attempts to explain the emergence of European and Latin American constitutional states of law. In legal theory, it highlights the contributions of some countries whose constitutional reforms or new charters integrated fundamental rights and high moral content. In this regard, it points out the rational, guaranteeing, and progressive role that judges should play under the principles and values that make up neoconstitutionalism.